Exposure to priority organochlorine contaminants in the Italian general population. Part 2: Fifteen priority polychlorinated biphenyl congeners in blood serum. (February 2014) - Mrema, EJ; Rubino, FM; Mandic-Rajcevic, S; Sturchio, E; Turci, R; Osculati, A; Brambilla, G; Minoia, C; Colosio, C
Concentrations of 36 polychlorinated biphenyl (PCB) congeners were measured in serum of 372 Italian residents of general population living in Novafeltria, Pavia, and Milan. Total PCB level differed significantly between these sites ( p  < 0.0001) with median concentrations of 836.50, 1354.57, and 2062.08 pmol/g lipid, respectively. However, there is no evidence for the difference in distribution of total PCB levels by genders. Total dioxin-like PCBs differed significantly ( p  < 0.0001) between the sites (median 109.78, 50.88, and 166.99 pmol/g lipid, respectively) and genders of Novafeltria and Pavia ( p  = 0.011 and 0.009, respectively). PCB 138, 153, 170, and 180 differed significantly between the places of residence ( p  < 0.0001) with higher values in Milan population. In the overall population, total PCB and PCB 138, 153, 156, 170, and 180 correlated positively with age (correlations range between 0.320 and 0.569, p  < 0.0001). In Novafeltria, the correlations ranged between 0.545 and 0.670, and in Pavia, the correlations ranged between 0.516 and 0.666. In Milan, correlations with age range between 0.327 and 0.417 for total PCB and congeners 138, 153, and 180. With an exception of PCB 170, there was no evidence of significant difference in the distribution of most abundant PCB congeners and total PCB across the body mass index categories.